2021
DOI: 10.34172/aim.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of COVID-19 Patients with Gastrointestinal Symptoms

Abstract: Background: We aimed to assess the gastrointestinal (GI) manifestations of patients with severe acute respiratory syndrome coronavirus 2 infection and determine factors predicting disease prognosis and severity among patients with GI symptoms. Methods: In this retrospective study, we evaluated laboratory confirmed (by real-time polymerase chain reaction) inpatient cases of coronavirus-associated disease 2019 (COVID-19), referred to Sina hospital, a tertiary educational hospital of Tehran University of Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…In addition, there was not a relationship between respiratory symptoms and GI manifestations in the study. 30 In line with these studies, Zhang et al 31 investigated the clinical characteristics of COVID-19 patients with GI symptoms from Wuhan in early 2020. They reported that 164 patients (32.5%) experienced GI symptoms, including appetence, diarrhea, nausea, abdominal pain, and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was not a relationship between respiratory symptoms and GI manifestations in the study. 30 In line with these studies, Zhang et al 31 investigated the clinical characteristics of COVID-19 patients with GI symptoms from Wuhan in early 2020. They reported that 164 patients (32.5%) experienced GI symptoms, including appetence, diarrhea, nausea, abdominal pain, and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that patients with isolated GI symptoms who test positive for PCR were less likely to be admitted to the ICU (95% CI: 0.174-0.987, P: 0.047). While studies by Montazeri et al (20) and Buscarini et al (21) did not find any relationship between the GI symptoms and ICU admission possibility. It might be due to the differences in the grouping of patients as these studies have categorized patients into GI and non-GI groups.…”
Section: Resultsmentioning
confidence: 76%
“…And OR values were < 1 in 7 [ 15 , 19 , 33 , 34 , 37 , 46 , 49 ] of these 8 literatures. On the other hand, 7 [ 12 , 16 , 18 , 25 , 29 , 36 , 57 ] of 13 Asian studies [ 12 , 16 , 18 , 25 , 29 , 30 , 36 , 38 , 40 , 43 , 50 , 52 , 57 ] reported that patients with GI symptoms were older, and OR values were > 1 in 6[ 12 , 16 , 25 , 29 , 36 , 57 ] of these 7 studies. It turns out that the studies carried out in different locations vary in the characteristics of included patients, especially in the age of patients with/without GI symptoms.…”
Section: Resultsmentioning
confidence: 99%